2009
DOI: 10.1021/jp909883b
|View full text |Cite
|
Sign up to set email alerts
|

Monolayer Orientation of ω-Substituted Amide-Bridged Alkanethiols on Gold

Abstract: A new set of aryl-substituted amides of 16-mercaptohexadecanoic acid (R ) 4-OCH 3 ; 3,5-di-OCH 3 ) are synthesized using a simple and general procedure. Self-assembled monolayers of these molecules on Au(111) are studied by infrared and visible ellipsometry and contact angle measurements. Model calculations are employed to determine the molecular tilt angle. The SAM methylene chains exist in prevailing all-trans conformation and the tilt of the CCC plane is decreased by approximately 15°in comparison with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…MD simulation of 1 SAM showed typical oriented thiol SAM arrangements, showing an angular distribution of the tilted angle centered on ∼30.5 • (averaged between the phenyl and alkyl tilt angles; see the supporting material available at stacks.iop.org/Nano/23/055605/mmedia), in good accordance with literature values (∼30 • ) [22]. Furthermore, the results from MD simulation demonstrate the formation of a strong network of H bonds between amide groups and 1 molecules, oriented parallel to the gold surface ( figure 3(B)) [23][24][25]. This confirms the importance of the design of the ligand as regards providing improved robustness for the GNR ligand shell [11].…”
Section: Figures 2(a) and (B) Show A Representative Uv-visiblesupporting
confidence: 85%
“…MD simulation of 1 SAM showed typical oriented thiol SAM arrangements, showing an angular distribution of the tilted angle centered on ∼30.5 • (averaged between the phenyl and alkyl tilt angles; see the supporting material available at stacks.iop.org/Nano/23/055605/mmedia), in good accordance with literature values (∼30 • ) [22]. Furthermore, the results from MD simulation demonstrate the formation of a strong network of H bonds between amide groups and 1 molecules, oriented parallel to the gold surface ( figure 3(B)) [23][24][25]. This confirms the importance of the design of the ligand as regards providing improved robustness for the GNR ligand shell [11].…”
Section: Figures 2(a) and (B) Show A Representative Uv-visiblesupporting
confidence: 85%
“…In the broad band region of the O–H stretching mode (3000–3500 cm –1 ), which may be from adsorbed water molecules in the QDA monolayer, a sharp peak is observed at 3320 cm –1 . According to previous studies, the N–H stretching without hydrogen bonding produces a peak around 3450 cm –1 . , The red-shift of this band to 3320 cm –1 implies that the hydrogen bonding is formed between the amide groups in the QDA monolayer. The SFG measurements on the N–H stretching mode of the protein or peptide, which is strongly hydrogen bonded, also show a peak around 3300 cm –1 . No significant difference in the peak position is observed for the N–H stretching mode of the QDA monolayer on the pure water subphase and 1 mM NaBr subphase (Figure a), indicating that the hydrogen bonding for the QDA monolayer prepared on the two subphases are not affected by the halide ions in the subphase.…”
Section: Results and Discussionmentioning
confidence: 70%
“…According to previous studies, the N−H stretching without hydrogen bonding produces a peak around 3450 cm −1 . 36,37 The red-shift of this band to 3320 cm −1 implies that the hydrogen bonding is formed between the amide groups in the QDA monolayer. 36−39 The SFG measurements on the N−H stretching mode of the protein or peptide, which is strongly hydrogen bonded, also show a peak around 3300 cm −1 .…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have concluded that SAMs made from alkanethiols containing secondary amides (HS­(CH 2 ) n CONHR) form well-ordered monolayers with strong intermolecular hydrogen bonding between neighboring amide groups throughout the backbone. SAMs made from amide-containing alkanethiols, like those made from simple alkanethiols, become more crystalline with increasing chain length. , The different physical states of amide-containing SAMs, however, occur at different chain lengths ( n ≈ 10–12) in comparison to n -alkanethiols ( n ≈ 12–14) and depend on the position of the amide group in the molecule. , …”
Section: Introductionmentioning
confidence: 99%